Information Technology Adoption And Operational Performance In State Tax Administration: Evidence From Osun State, Nigeria - Yusuf Alabi Olumoh; Mubaraq Sanni (Universitas Indonesia Membangun, 2025)
The modernization of tax administration through information technology (IT) has become critical for improving the operational performance of tax authorities globally. Many States Internal Revenue Services have been encountering challenges on adoption and implementation of information technologies in tax processes, collections and compliance, due to its complexities, weak tax legislation and enforcement, which in turn reduce the operational performance of state revenue agencies. Given these issues, this study examines the role of IT adoption in enhancing the operational performance in the Osun State Tax Administration. The study population comprised 528 staff of Osun State Internal Revenue Service (OIRS), and using Taro Yamane's formula, a sample size of 228 was determined. Data was collected through a structured questionnaire and analyzed using Covariance-Based Structural Equation Modeling (CB-SEM). The study’s path coefficient result of 0.913 showed a strong and statistically significant positive relationship between Information Technology and operational performance. The study concludes that the adoption of modern IT solutions is crucial to the effectiveness of tax administration in Osun State. It demonstrates that investments in technology not only improve internal operational processes but also build public trust and compliance among taxpayers. The study recommends that OIRS and similar revenue agencies in Nigeria enhance operational performance and ensure sustainable revenue growth by investing in robust digital infrastructure and cybersecurity frameworks to safeguard taxpayer data; promoting taxpayer education to boost digital literacy and engagement; and strengthening strategic partnerships with technology providers alongside regular capacity-building initiatives for staff.